VISI AL-QUR’AN TENTANG PRODUKSI : (Eksplorasi Ayat-Ayat al-Qur’an Melalui Kata-Kata Kunci) - Rusdan; Alim, Sahirul (MUSLIMPRENEUR : Jurnal Ekonomi dan Kajian Keislaman, 2024)
A natural process that began on earth with the arrival of humanity is called production. Producing becomes essential to human culture, earthly survival, and even life itself. Production is understood as bringing utility to that use and/or as increasing its value. Producing, on the other hand, involves placing use if consuming means taking something's use-value. The Quran as referenced in QS. al-An'am (6): 38 does not overlook anything, even in the broad framework, including concerns with regard to production activity. Descriptive analytic qualitative research approach is the technique employed. While the method utilized is library research with an emphasis on economic interpretation of the Quran, which operationally goes through four steps, namely: First, finding verses that highlight production difficulties based on key terms. The second is elaborating on the meaning of scriptures pertaining to production using information from diverse commentaries. Third, combine interpretation analysis with economists' points of view. Fourth, do economic reality contextualization. Al-intaj, kasab, ishlah, 'imarah, and ihtiraf are Arabic names for production. These words are used by the Quran in numerous tenses, with the exception of the word al-intaj. The employment of these phrases is not always indicative of production activity, though. It is possible to infer a number of things from the three verses that correspond to the words kasab, ishlah, and 'imarah. Land and labor are listed as the primary producers in the Quran. Second, the social roles that work and land play cannot be separated. Third, there must be no pollution or harm to the cosmos as a result of production activity. Fourth, it is decided that one of the most significant soft skills supporting components of work output is faith and piety.